A hazard-perception test for cycling children: An exploratory study. (August 2016) - Vansteenkiste, Pieter; Zeuwts, Linus; Cardon, Greet; Lenoir, Matthieu
Highlights: Situational awareness and hazard perception in child cyclists are discussed. Children are suggested to respond slower to hazards. Children might have difficulties interpreting the necessary information. Development of a future hazard perception test for cyclists is discussed. Abstract: In car driving, hazard perception tests have revealed important differences in perceptual-cognitive skills between novice and experienced drivers. Although these insights have led to new educational programs for learner drivers, similar research has not yet been done for other road users such as bicyclists. In the current investigation, a first hazard perception test for bicyclists has been developed and tested on both adults and children of ±eight year old. The test consisted of three sections in which visual behaviour, environmental awareness, and risk perception were evaluated respectively. Although only few differences in visual behaviour and environmental awareness were found, adults were found to react earlier on hazards than children. These results suggest that children have difficulties to interpret the necessary information to react timely to hazardous traffic situations. Alternatively, the current set-up of the hazard perception test might not have been suitable to detect differences in visual behaviour between children and adults in traffic situations. Therefore the development and use of future hazard perception tests for bicyclists is discussed.